(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Mexican modernism is a movement that provides important insights both to the history of the Mexican aesthetics, as well as to the relection and to the construction of the image of what is “Mexican”. he reassessment of Mexican modernism enables veriication that the revolutionary period does not necessarily represent, much less as it was intended, a rupture in the construction of a narrative and of a national identity with respect to the immediately preceding period. Issues such as indigenism, miscegenation and the very idea of nation are developed even more in the Poririate. However, modernism is also an original and peculiar movement, and given that its relation to the image is less sacralized and freer than in previous and subsequent periods. his allows it to acquire two rare traits, particularly in painters like Julio Ruelas and Saturnino Herrán: irst of all, a great opening and reception of international art and to its diversity of styles; and secondly, an equally desacralized and nonideological dialogue between the diverse arts and eras.